PROGNOSTIC SIGNIFICANCE OF ENDOTHELIAL DYSFUNCTION MARKERS IN ARTERIAL HYPERTENSION - V. I. Podzolkov; A. E. Bragina; N. A. Bragina (Российский кардиологический журнал)
Aim. Assessment of prognostic significance of endothelial dysfunction markers: stable metabolites of nitric oxide (NOx), von Willebrand factor (vWF), endothelin-1 (E1), homocysteine and tissue plasminogen activator (tPA) in essential hypertension (EAH) patients not taking antihypertension therapy systematically.Material  and  methods. Totally, 12 EAH patients investigated (45 males, 79 females) (mean age 51,4±6,5 y. o., mean duration of AH 7,9±7,3 y.). Concentration of NOx in plasma was measured by spectrophotometry, and of vWF, homocysteine, E1 and tPA — by immune enzyme assay.Results. By the increase of SCORE risk level, there was significant increase of concentrations of NOx, E1, homocysteine and vWF in EAH patients (p<0,05), there were no changes in tPA levels (p>0,05). In 8 (8±1,1) years after baseline assessment, 115 patients were assessed second time. Of those 13 (11,3%) had cardiovascular events (CVE) and 5 (4,3%) died. By single factorial regression, the rate of CVE in EAH patients relate to homocystein level (р=0,01), NOx (р=0,001) and vWF (р=0,001). By multifactorial analysis, prognostic statistical significance is found for NOx (relative risk (RR) =3,8, р=0,006) and vWF (RR =3,5, р=0,005). In ROC-analysis there were found threshold levels of NOx (>46,6 mcM/L, AUC =0,863) and vWF (>1,68 mg/dL, AUC =0,738), the increase of which is followed by CVE development risk for the levels of NOx >46,6 mcM/L 3,8 times (sensitivity 81,9% and specificity 65,8%), vWF >1,68 mg/dL — 3,5 times (sensitivity 74,3% and specificity 62,7%). Combination of the parameters point on the risk increase up to 6,5 times (р=0,00007).Conclusion. NOx with the threshold of >46,6 mcM/L (RR =3,8) and vWF >1,68 mg/dL (RR =3,5) do show independent prognostic value for 5-year CVE risk assessment in EAH patients that can be applied as an additional method for risk stratification to estimate a group for more aggressive therapy and CVE prevention.